2012
DOI: 10.1021/nn204654h
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Tuned Self-Organization of a Bulk Heterojunction Hybrid Solar Cell with Enhanced Performance

Abstract: We demonstrate here that the nanostructure of poly(3-hexylthiophene) and [6,6]-phenyl-C61-butyric acid methyl ester (P3HT/PCBM) bulk heterojunction (BHJ) can be tuned by inorganic nanoparticles (INPs) for enhanced solar cell performance. The self-organized nanostructural evolution of P3HT/PCBM/INPs thin films was investigated by using simultaneous grazing-incidence small-angle X-ray scattering (GISAXS) and grazing-incidence wide-angle X-ray scattering (GIWAXS) technique. Including INPs into P3HT/PCBM leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 40 publications
3
80
1
Order By: Relevance
“…8,9 Furthermore recent studies demonstrated that the NPs can lead to an enhancement of the OPV device structural stability as well. [10][11][12] Methods to synthesize and incorporate MNPs are in abundance. Chemical synthesis can give precise control of size, however, it produces a lot of hazardour wastes, 13,14 with a requirement of an additional process step for deposition.…”
mentioning
confidence: 99%
“…8,9 Furthermore recent studies demonstrated that the NPs can lead to an enhancement of the OPV device structural stability as well. [10][11][12] Methods to synthesize and incorporate MNPs are in abundance. Chemical synthesis can give precise control of size, however, it produces a lot of hazardour wastes, 13,14 with a requirement of an additional process step for deposition.…”
mentioning
confidence: 99%
“…The lamellar spacing of P3HT crystallites after annealing at 130°C is larger than that annealed at lower temperatures, as evidenced by the shift of peak toward low angles. It is suggested that the expansion effect is due to the intercalation of PCBM or 8OCB molecules between lamellar layers [38].…”
Section: Resultsmentioning
confidence: 99%
“…This work was subsequently investigated by employing powerful grazing incidence wide/small angle X-ray scattering (GIWAXS/GISXAS) technique (Figure 7c) to explore the morphological evolutions and mechanisms in which the findings beyond the knowledge at that time were pointed out [63]. The GIWAXS/GISAXS technique with modeling has been intensively utilized to quantitatively characterize the nanostructures of BHJ blend films [24,64,65]. Referring to the established insights into the P3HT/PC61BM BHJ system [64], the P3HT/PC61BM blend film is generally comprised of three kinds of structures: (1) P3HT crystallites; (2) PC61BM clusters with size of 10-20 nm and (3) meso-scaled domains of amorphous P3HT chains intercalated with PC61BM molecules (denoted as PC61BM/amorphous P3HT).…”
Section: Small Moleculesmentioning
confidence: 99%
“…Inorganic nanocrystals (INCs) can also be included into BHJ film, which is an extensively adopted strategy to enhance device performances [65][66][67][68][69]. The main focus lies on their unique plasma effects for enhancing light scattering path within the thin films.…”
Section: Inorganic Nanocrystalsmentioning
confidence: 99%
See 1 more Smart Citation